Internship Report and Monography entitled “State-of-the-Art of Research and Development of Dendritic Cells Vaccines in the Treatment of Alzheimer’s Disease” - Ferreira, Rafael Soares (2021)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia